Rail trails literature: Current status and future research. (1st January 2021) - Scherrer, Pascal; Dimmock, Kay; Lamont, Matthew; Ripoll González, Laura
Abstract: Rail trail developments involve converting disused railway corridors into multi-use spaces for leisure, tourism, and sustainable mobility. The transformation of disused railway corridors into successful rail trail developments in the United States, New Zealand and the United Kingdom has contributed to a resurgence in community, government and business interest in developing rail trails in other countries. As evident from several jurisdictions, rail trail development has the potential to spark debates around fundamental issues related to prudent use of dormant public assets, namely railway corridors. This exploratory systematic review examined peer-reviewed studies of rail trails published in English language academic journals to examine the substance, extent and research gaps of this distinct subset of the broader literature on trails. A fledgling, fragmented body of knowledge was identified, spanning themes from planning, management and user experience to social, economic and environmental impacts of rail trails. Directions for future research are provided.